PATHOGENETIC SUBSTANTIATION HEPATOPROTECTIVE THERAPY IN PATIENTS WITH THYROID PATHOLOGIES - Скрипник, Н. В.; Вацеба, Т. В. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
The review of sience works devoted to modern views on the liver disease pathogenetic mechanisms and hepatoprotective therapy study in patients with thyroid gland disorders. This article presents the literature data, showing that the hepatobiliary system plays an important role in endocrine status supporting. Liver provided thyroid gland hyperfunction caused by increased secretion of thyroxine and triiodothyronine, effects on mitochondrial apparatus of hepatocytes hepatotoxic influence thyreostatics, prolonged heart failure in the thyrotoxic heart development. Pathogenetic mechanisms of liver dysfunction in hypothyroidism is relatively perivenular hypoxia, lipid metabolism, decreased excretion of bilirubin and bile; weakening reutilization iodine and the development of relative iodine deficiency. Violation of the hepatobiliary system can be considered as a clinical manifestation of hypothyroidism which requiring active hepatoprotective therapy simultaneously with the appointment of hormone replacement therapy.